Frequency of indiference to the dental treatment in adults from 18 to 44 years old Totoracocha, Cuenca-Ecuador, 2017 - Fernández Siguencia, María José (2021)
ABSTRACT Objective: To determine the frequency of indifference to dental treatment in young adults aged 18 to 44, from the Totoracocha parish, Cuenca-Ecuador, 2017. Materials and Methods: A quantitative study with a descriptive cross-sectional design was carried out in individuals of both sexes. , between the ages of 18 to 44 years to whom the Nuttall DIS survey was applied, the sample size was calculated with the probabilistic, stratified and proportional sampling formula, plus 10% for loss effects, surveying 586 persons. The information was entered into the EPI Info 7 database, discarding the surveys that did not present informed consent, that had studs, and age groups not belonging to the corresponding age, the information was reviewed by the research area of the dental career . Regarding ethical aspects, the research was approved by the ethics committee of the Catholic University of Cuenca, Faculty of Dentistry. Results: The frequency of indifference to the dental treatment that was presented in the Totoracocha parish was 76.% of the population surveyed, where the condition for men was 39% and for women it was 37%, the main cause Indifference was the lack of time with a percentage of 23%. Conclusion: More than 50% of respondents presented indifference to dental treatment where the most important factor was the lack of time.